2013
DOI: 10.1172/jci67364
|View full text |Cite
|
Sign up to set email alerts
|

Fanconi anemia signaling network regulates the spindle assembly checkpoint

Abstract: Fanconi anemia (FA) is a heterogenous genetic disease with a high risk of cancer. The FA proteins are essential for interphase DNA damage repair; however, it is incompletely understood why FA-deficient cells also develop gross aneuploidy, leading to cancer. Here, we systematically evaluated the role of the FA proteins in chromosome segregation through functional RNAi screens and analysis of primary cells from patients with FA. We found that FA signaling is essential for the spindle assembly checkpoint and is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(89 citation statements)
references
References 43 publications
7
82
0
Order By: Relevance
“…i) Recent studies have shown that several DNA repair proteins localize to the centrosome, and defects in these proteins cause several functional aberrations in centrosomes such as centrosome amplification. [40][41][42][43] Also, it has been shown that DNA damage can induce centrosome amplification. [41][42][43] Overexpression of Usp1 in NIH3T3 cells inhibited UV-induced Fancd2-Ub and PCNA-Ub (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…i) Recent studies have shown that several DNA repair proteins localize to the centrosome, and defects in these proteins cause several functional aberrations in centrosomes such as centrosome amplification. [40][41][42][43] Also, it has been shown that DNA damage can induce centrosome amplification. [41][42][43] Overexpression of Usp1 in NIH3T3 cells inhibited UV-induced Fancd2-Ub and PCNA-Ub (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several FA proteins localize to centrosomes and the mitotic spindle. 98,101 DNA damage response and FA: ATM, ATR, and CHK1…”
Section: Fa Pathway and Cytokinesismentioning
confidence: 99%
“…Consistent with our findings, Nalepa and colleagues also observed a higher percentage of fibroblast cells taken from FA patients including FancJ patients showing centrosome amplification compared to that from healthy individuals. 40 Though the exact physiological implication is still unknown, DDICA is thought to be another fail-safe mechanism to commit cells experiencing severe DNA damages to cell death and thereby plays a potential role in suppressing tumorigenesis. 10 Here we showed that deficiency of BRCA1 induces centrosome amplification in non-stressed cells as previously reported while attenuating both HU-and MMC-induced centrosome amplification.…”
Section: Introductionmentioning
confidence: 99%